2000
DOI: 10.1145/373975.373984
|View full text |Cite
|
Sign up to set email alerts
|

Software cost estimation with fuzzy models

Abstract: Estimation of effort/cost required for development of software products is inherently associated with uncertainty. In this paper, we are concerned with a fuzzy set-based generalization of the COCOMO model (f-COCOMO). The inputs of the standard COCOMO model include an estimation of project size and an evaluation of other parameters. Rather than using a single number, the software size can be regarded as a fuzzy set (fuzzy number) yielding the cost estimate also in form of a fuzzy set. The paper includes detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…It has been found that the most accurate prediction models are based on analogy and experts opinion. Expertbased estimation was also found to be better than all regression-based models [3]. Henceforth the use of fuzzy logic in reusability prediction is desirable since expert knowledge can be incorporated into the fuzzy reusability prediction models.…”
Section: Fuzzy Techniquementioning
confidence: 93%
See 1 more Smart Citation
“…It has been found that the most accurate prediction models are based on analogy and experts opinion. Expertbased estimation was also found to be better than all regression-based models [3]. Henceforth the use of fuzzy logic in reusability prediction is desirable since expert knowledge can be incorporated into the fuzzy reusability prediction models.…”
Section: Fuzzy Techniquementioning
confidence: 93%
“…al. [3] to access the reusability of components but the author never applied the concept to use the approaches across the releases of components as well as not the neuro-fuzzy approach. It is proven in many proposed techniques that neuro-fuzzy give the better results as compare to standalone FIS or ANN because it uses the power of rules decision of FIS and adaptive nature of ANN in a single system together.…”
Section: Proposed Anfis Approachmentioning
confidence: 99%
“…This approach does not appear to perform well over other datasets that are not structurally similar to COCOMO dataset, and it is no suitable for early stage estimation. Musflek et al (2000) developed a granular model for software cost estimation based on Fuzzy number called f-COCOMO. Both input (kilo line of code) and output (effort) are represented by their corresponding triangular Fuzzy numbers.…”
Section: Related Workmentioning
confidence: 99%
“…Musflek et al worked on fuzzifying basic COCOMO model without considering the adjustment factor [15]. In their simple f-COCOMO model, the size input into the COCOMO model is represented by a fuzzy set, while a and b coefficients are crisp values.…”
Section: Fuzzy Logic In Algorithmic Modelsmentioning
confidence: 99%
“…The use of fuzzy set supports continuous belongingness (membership) of elements to a given concept (such as small software project) [22] thus alleviating a dichotomy problem (yes/no) [15] that caused similar projects having different estimated efforts.…”
Section: Why Fuzzy Logic?mentioning
confidence: 99%